Effect of dietary supplemental chromium on nutrient utilization, rumen metabolites and enzyme activities in fistulated crossbred male cattle - Rikhari, Kusum; Tiwari, D P; Kumar, Anil (The Indian Journal of Animal Sciences, 2011)
The experiment was conducted to ascertain effect of different levels of dietary supplementation of chromium (Cr) on nutrient utilization, ruminal enzyme activities and fermentation pattern. Adult fistulated male crossbred cattle (3) were supplemented with chromium as chromium picolinate in a 3×3 latin square switch-over design, viz. treatment 1, control (without chromium supplementation), treatment 2 (0.5 mg chromium/kg diet dry matter as chromium picolinate), and treatment 3 (1.0 mg chromium/kg diet dry matter as chromium picolinate). There was no significant effect on dry matter, total digestible nutrients and digestible crude protein intakes and digestibility of different nutrients due to supplementation of chromium. The mean concentration of total nitrogen and non-protein nitrogen in SRL was significantly higher in T2 supplemented with 0.5 mg Cr/kg DM than in T3 supplemented with 1.0 mg Cr/kg DM, while TCAprecipitable protein nitrogen and ammonia nitrogen concentrations did not differ significantly among the treatments. No significant difference was observed in TVFA concentration among the treatments. However, all the rumen biochemical parameters differed significantly due to time interval of sampling of rumen liquor. The different fractions of whole rumen content, viz. particulate material (PM), cellular fraction (C) and extra cellular fraction (EC) exhibited no significant effect on activity of carboxymethyl cellulase, α-amylase, xylanase, α-glucosidase and ß-glucosidase in rumen content with different levels of chromium supplementation. Activity of all enzymes was higher in particulate material fraction as compared to cellular fraction and extra cellular fraction. It is concluded that 0.5 to 1.0 mg chromium supplementation per kg diet dry matter as chromium picolinate had no effect on feed intake, nutrient utilization, ruminal metabolic profile and enzyme activities in crossbred male cattle.